Deficiency of proteins and ways its solution - Fursik, Oksana; Strashynskyi, Igor; Pasichnyi, Vasyl (My University, 2019)
Consumption the required amount of protein is a fundamental factor in human health. The protein needs can be met by the complex consumption of animal and plant foods. The obtained data on the study of the amino acid composition show that the use of the functional composition containing protein increases the amount of essential amino acids of the experimental cooked sausages to the established level in accordance with the needs of the person and balances them, as evidenced by the criterion of the imbalance amino acid composition.
Keywords: кафедра технології м’яса і м’ясних продуктів; амінокислотний склад; білоквмісна композиція; варена ковбаса